INVESTIGATION OF THE NON-DRYING ABILITY AND DEFORMABILITY OF REBAR JOINTS WITH WOOD WHEN PULLING OUT - Makhmatkulov Turdimurod; Turdimurodov Jasur Ilhomovich (Scholar Express Journals, 2021)
The responsible node of the wooden glued columns is the support node, rigidly connected to the foundations. The strength and deformability of the support unit connected to the foundation with the help of glued rods depends on the action of the longitudinal force and bending moment. The article presents experimental data of connections on glued rods when pulling out
Keywords: Wooden glued column; responsible node; glued metal rod; test results